A role for multiple estrogen receptors in immune regulation of common carp. (January 2017) - Szwejser, Ewa; Maciuszek, Magdalena; Casanova-Nakayama, Ayako; Segner, Helmut; Verburg-van Kemenade, B.M. Lidy; Chadzinska, Magdalena
Abstract: Estrogens are important for bi-directional neuroendocrine-immune interaction. They act via nuclear estrogen receptors (ERα and ERβ) and/or G-protein coupled receptor - GPR30. We found expression of ERα, ERβ and GPR30 in carp lymphoid tissues and head kidney monocytes/macrophages, neutrophils and lymphocytes. Interestingly, ERβ is also expressed in some head kidney lymphocytes but not in naive PBLs. Immune stimulation altered the cell type specific profile of expression of these receptors, which depends on both activation and maturation stage. This implies direct leukocyte responsiveness to estrogen stimulation and therefore in vitro effects of 17β-estradiol (E2) on reactive oxygen species (ROS) production in monocytes/macrophages were determined. Short-time incubation with E2 increased ROS production in PMA-stimulated cells. Results comply with mediation by GPR30, partially functioning via phosphoinositide 3-kinase activation. These results furthermore demonstrate that neuroendocrine-immune communication via estrogen receptors is evolutionary conserved. Highlights: Carp leukocytes express nuclear – ER and membrane - GPR30 estrogen receptors. erβ is not-detectable in naïve PBL's. Immunostimulation alters the expression of estrogen receptors. E2-induced changes in ROS production are mediated by GPR30. Neuroendocrine-immune interaction via estrogen receptors is evolutionary conserved.